Synthesis of CeO2-Fe2O3 Mixed Oxides for Low-Temperature Carbon Monoxide Oxidation - Chuc Ngoc Pham; Quyen Van Trinh; Dang Van Thai; Nhiem Ngoc Dao; Bac Quang Nguyen; Dung Trung Doan; Hung Bao Le; Vinh Van Nguyen; Lim Thi Duong; Lam Dai Tran (Adsorption Science & Technology)
In this study, the CeO2-Fe2O3 mixed oxide catalysts have been prepared by combustion method using gel-created tartaric acid. The ability of effective carbon monoxide (CO) oxidation to carbon dioxide (CO2) by CeO2-Fe2O3 catalyst under low-temperature conditions was also demonstrated. The calcined CeO2-Fe2O3 material has a porous honeycomb structure and good gaseous absorption-desorption ability. The solid solution of CeO2-Fe2O3 mixed oxides was formed by the substitution of Fe+3 ions at some Ce4+ ion sites within the CeO2 crystal lattice. The results also showed that the calcination temperature and the molar ratio of Ce3+ ions to Fe3+ ions (CF) affected the formation of the structural phase and the catalytic efficiency. The catalytic properties of the CeO2-Fe2O3 mixed oxide were good at the CF ratio of 1 : 1, the average crystal size was near 70 nm, and the specific surface area was about 20.22 m2.g-1. The full conversion of CO into CO2 has been accomplished at a relatively low temperature of 270 °C under insufficient O2 conditions.